2011
DOI: 10.1093/europace/eur036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pulmonary veins isolation by cryoablation for the treatment of paroxysmal and persistent atrial fibrillation

Abstract: Pulmonary vein isolation, using a cryoballoon catheter, was completed with a high rate of procedural and long-term success and low rate of minor complications. Supplemented, when needed, by focal RF, cryoballoon ablation was a safe and an effective alternative to a circumferential RF procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 31 publications
5
29
0
Order By: Relevance
“…However, it did not reach the statistical significance in a multivariate Cox regression analysis. Similar results have been presented in several studies using cryoballoon technique for PVI [6,7,9]. These results suggest that cryoballoon PVI itself is less sufficient for the treatment of even early persistent AF.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, it did not reach the statistical significance in a multivariate Cox regression analysis. Similar results have been presented in several studies using cryoballoon technique for PVI [6,7,9]. These results suggest that cryoballoon PVI itself is less sufficient for the treatment of even early persistent AF.…”
Section: Discussionsupporting
confidence: 88%
“…At 6, 12, 24, and 36 months of follow-up (respectively), 93, 78, 53, and 34 % of the paroxysmal AF patients had remained free of documented AF. By comparison, 77, 54, 34, and 18 % of the [6][7][8][9][10]. In this study 78 , 53,and 34 % of patients with paroxysmal AF were free from AF within 12, 24, and 36 months, respectively.…”
Section: Long-term Outcomesmentioning
confidence: 61%
See 1 more Smart Citation
“…These results compare with the previously quoted rates of 47-78% at three years for freedom from AF with radiofrequency ablation [4][5][6][7]. Recent studies also using cryoballoon ablation have shown rates of freedom from paroxysmal AF of 74% at 18 months [8], 69% at 12 months [15], 52.5% at a mean of nine months [11] and 70% at a mean of nine months [10]. These trials all used symptomatic recurrence as an end point with differing degrees of routine telemetry monitoring.…”
Section: Discussionsupporting
confidence: 69%
“…11 Immediate and midterm follow-up studies have revealed that its efficacy is similar to that of radiofrequency ablation. [12][13][14][15][16] Although some cases of PV stenosis after cryoballoon ablation have been reported, 17,18 the influence of cryoballoon ablation on the morphology of the PV is unknown. The purpose of this study was to evaluate the influence of cryoballoon ablation on the morphology of the PV and to investigate the factors associated with PV narrowing.…”
mentioning
confidence: 99%